Special Collection Management System - Muhamad Mirza Kamar,; Juhaida Abu Bakar,; Norliza Katuk, (Multidisciplinary Applied Research and Innovation, 2021)
There are a hundred thousand items with over 200,000 volumes circulated every year in the Sultanah Bahiyah UUM library. The transaction was recorded in books before the change to computerized led to a missing file and record. In this project, our objective is to develop a Special Collection Management System which efficiently registers special materials collections in UUM. Special collections are rare and valuable items that do not have any additional prints as they came from the original source. There are three types of special material collections, which are manuscripts, character writing and valuable images. In Sultanah Bahiyah library, the special collections are not available to be borrowed. Users who need to use special collection materials must use them at the library desk. This situation shows that special collection materials are very hard to access remotely from home or office. The sub-objectives are as follows: 1) to identify system requirements for the Special Collection Management System; 2) to develop a web-based Special Collection Management System with a Rapid Application Development (RAD) methodology; and 3) to test and evaluate the usability of the Special Collection Management System using the Technology Acceptance Model (TAM). The Rapid Application Development (RAD) methodology model has been used for the project methodology. There are four phases in RAD, namely requirement planning, prototyping, testing, and cutover. The finding shows that 80 percent agreed with the usefulness of the Special Collection Management System. This invention can assist the UUM staff library in managing special materials in a more structured manner.